Desain Pengembangan Pembelajaran Pendidikan Agama Islam di Sekolah dan Madrasah - Muhamad Tanthowi Jauhari (Pendidikan Agama Islam STIT Palapa Nusantara, 2020)
Models and learning strategies that override the structure of learning content so that the material delivered by the teacher, does not last long in students' memories. The purpose of this paper is to find out the steps in organizing, establishing, and developing strategies for organizing the contents of religious education learning through the design of professional Islamic religious education learning. Meanwhile, the theory used in this problem is to use the theory of learning design models that refer to the systems approach, which is developed by Kemp, Dick and Carey, and the Dageng model, all of which include analysis of learning conditions, development of learning strategies, and development of measurement procedures learning. This paper is a research type of library reaserch, which is descriptive analytical. The method of thinking in this paper uses the inductive method in which the discussion is to analyze data from facts that are specific to general facts about the design of the development of PAI learning.The results of this paper study show that: (1) The design of the development of PAI learning by using the Kemp model rests on four basic elements of learning planning, namely students, objectives, methods, and evaluation. The design model of Dick and Carey's development refers to the system approach and Degeng's development design model is based on variables that influence learning in the form of objectives and characteristics of the field of study, learning resources and constraints, learner characteristics, learning objectives and learning content, strategies for organizing learning contents, delivery strategies learning content, learning management strategies, developing learning outcomes measurement procedures. (2) The steps in the design of the development of PAI learning in schools and madrassas include: analysis of competency standards, learning materials, characteristics of students, selecting and defining approaches and evaluating learning outcomes.